Pediatric surgical aortic arch repair. With heart and mind - Rueffer, A. (Zeitschrift für Herz-, Thorax- und Gefäßchirurgie, 2019)
The research series addresses myocardial and cerebral protection during surgical repair of congenital aortic arch malformations. 1.The beating heart (BH) technique during aortic arch repair is associated with improved contractility compared with standard crystalloid cardioplegia after disconnecting the heart-lung machine; however, it is recommended that this technically complicated procedure should be curtailed when there is any evidence of ischemic changes and if necessary to switch to a cardioplegic cessation of the heartbeat. 2.The intraoperatively combined transfontanellar-transtemporal Doppler sonography is auseful tool to visualize the circle of Willis and the intensity of cerebral vessel perfusion during aortic arch repair. By the direct comparison of effective cerebral blood flow, the hypothesis of ahomogeneous distribution of cerebral blood flow to both hemispheres during regional cerebral perfusion is reinforced by this study.
CRIS-Team WoS Importer:2019-02-21